Comparative analysis of amplicon and metagenomic sequencing methods reveals key features in the evolution of animal metaorganisms - Rausch, Philipp (Microbiome, 2019)
BACKGROUND: The interplay between hosts and their associated microbiome is now recognized as a fundamental basis of the ecology, evolution, and development of both players. These interdependencies inspired a new view of multicellular organisms as “metaorganisms.” The goal of the Collaborative Research Center “Origin and Function of Metaorganisms” is to understand why and how microbial communities form long-term associations with hosts from diverse taxonomic groups, ranging from sponges to humans in addition to plants. METHODS: In order to optimize the choice of analysis procedures, which may differ according to the host organism and question at hand, we systematically compared the two main technical approaches for profiling microbial communities, 16S rRNA gene amplicon and metagenomic shotgun sequencing across our panel of ten host taxa. This includes two commonly used 16S rRNA gene regions and two amplification procedures, thus totaling five different microbial profiles per host sample. CONCLUSION: While 16S rRNA gene-based analyses are subject to much skepticism, we demonstrate that many aspects of bacterial community characterization are consistent across methods. The resulting insight facilitates the selection of appropriate methods across a wide range of host taxa. Overall, we recommend single- over multi-step amplification procedures, and although exceptions and trade-offs exist, the V3 V4 over the V1 V2 region of the 16S rRNA gene. Finally, by contrasting taxonomic and functional profiles and performing phylogenetic analysis, we provide important and novel insight into broad evolutionary patterns among metaorganisms, whereby the transition of animals from an aquatic to a terrestrial habitat marks a major event in the evolution of host-associated microbial composition. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40168-019-0743-1) contains supplementary material, which is available to authorized users.